Determination of tritium activity concentration in natural water samples - Karataşlı M.; Ş, Turhan; Kurnaz A.; Varinlioğlu A.; Gören E.; Yeğingil Z. (Informa UK Limited, 2017)
ABSTRACTThis study aims to measure tritium activity concentrations in tap, well, and spring water samples from Mersin province in Turkey using a liquid scintillation counting (LSC) system and to evaluate the corresponding radiological hazards due to the ingestion of water samples. The tritium activity concentrations measured in the water samples varied from < 1.9 (detection limit) to 14.1 ± 1.0 Bq L−1 (119.5 ± 8.5 TU) with an average of 6.2 ± 0.6 Bq L−1 (52.5 ± 5.4 TU). The tritium activities in the water samples were significantly lower than the limit of 100 Bq L−1 for water intended for human consumption. The annual effective doses estimated for different age groups of the members of the public due to the intake of the tritium varied from 0.009 to 0.185 μSv y−1.
Keywords: tap water; well water; annual effective dose; Tritium; liquid scintillation counting; 13. Climate action; 6. Clean water